Team Viability Relationship with Quiet Quitting and Career Satisfaction in Knowledge Workers Teams - Kukytė, Aistė (Vilnius University Proceedings, 2025)
This study analyses the role of team viability in quiet quitting and career satisfaction. Understanding the core principles of viable teams and disengaged team members or being satisfied with their careers could enable organisations to be more adaptable to the workforce. An empirical study was conducted on a sample of 207 knowledge workers from various organisations. The results of the multiple regression analysis suggest that team viability has a significant negative relationship with quiet quitting, and a significant positive relationship with career satisfaction. The mediation analysis results showed that career satisfaction mediated the relationship between team viability and quiet quitting. The study provided insights about viable team members participating in lower quiet quitting behaviours, and if those team members feel satisfied with their careers, quiet quitting behaviours are even lower.